Postural stability and plantar pressure parameters in healthy subjects: variability, correlation analysis and differences under open and closed eye conditions - De Blasiis, P.; Caravaggi, P.; Fullin, A.; Leardini, A.; Lucariello, A.; Perna, A.; Guerra, G.; De Luca, A. (Frontiers in Bioengineering and Biotechnology, 2023)
The “Postural Control System” acts through biomechanical strategies and functional neuromuscular adaptations to maintain body balance in static and dynamic conditions. Postural stability and body weight distribution can be affected by external sensory inputs, such as different visual stimuli. Little knowledge is available on the influence of visual receptors on stabilometric and plantar pressure parameters. The aim of this study was to analyse variability, correlations and changes of these parameters in open (OE) and closed (CE) eyes conditions. 31 stabilometric and plantar pressure parameters were acquired in 20 young and heathy adults during baropodometric examination performed in bipedal standing in both visual conditions. Variability of parameters was evaluated via coefficient of variation, correlation analysis via Pearson R2 and statistical differences via Wilcoxon test. High intra-subject repeatability was found for all plantar pressure parameters and CoP-speed (CV<40%) in OE and CE, while CoP-sway area (CoPsa) and Length Surface Function (LSF) showed larger variability (CV>50%). Mean and peak pressure at midfoot and total foot load showed the least number of significant correlations with other parameters in both visual conditions, whereas the arch-index and rearfoot load showed the largest number of significant correlations. Limb side significantly affected most plantar pressure parameters. A trend of larger LSF and lower CoPsa, mean and peak pressures at the right forefoot were found in CE. The present study provides a deeper insight into the associations between postural stability and foot load. Interesting postural adaptations, in particular with respect to different visual stimuli, the effect of the dominant side and the specific role of the midfoot in balance control were highlighted.